BIOETIKA PENELITIAN BIOEKOLOGI TUMBUHAN POHON CEMARA (Casuarina sp.) DI PANTAI KURANJI, KABUPATEN LOMBOK BARAT - Karisma Cahyani; Oktavita wulandari; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Casuarina trees (Casuarina sp.) are a key element of coastal flora, significantly contributing to the stability of shorelines and the equilibrium of ecosystems. Nevertheless, research in bioecology conducted in natural settings can present risks to ecosystems if ethical considerations are not thoroughly observed. This research intends to examine the implementation of bioethical principles in bioecological studies concerning Casuarina trees at Kuranji Beach, located in West Lombok. The study utilized a qualitative descriptive method through observational techniques and ethical evaluation without any quantitative data collection. Findings reveal that bioethical principles can be incorporated through approaches that do not harm the environment, maintain the integrity of habitats, and foster ecological awareness during research efforts. Moreover, the research highlights possible infringements of bioethical standards observed in field studies where there is a deficiency in ethical consciousness. Consequently, the inclusion of bioethical principles is crucial for ensuring that research activities are performed in a responsible and sustainable manner, especially in coastal ecosystems that are particularly susceptible to ecological disturbances.